Cenário atual das práticas de reabilitação funcional de adultos pela terapia ocupacional no Brasil - Finarde, Tamara Neves (Universidade Federal de São Carlos, 2025)
Occupational Therapy practices in the field of physical rehabilitation in Brazil have historically been grounded in a set of profession-specific knowledge, while also being influenced by service demands, the advancement of scientific evidence, and national and international policies. The perspectives of theoretical models and practical frameworks also guide these practices, in alignment with academic production. This study aims to characterize the professional practice of occupational therapists working in adult physical rehabilitation in Brazil. It is a quantitative and qualitative study with a descriptive and exploratory design, conducted in two phases. The first phase consisted of data collection through a self-administered semi-structured questionnaire, developed by a group of researchers and made available online via Google Forms®. The second phase involved semi-structured interviews. In the first phase, the sample consisted of 109 occupational therapists with undergraduate degrees who work in adult physical rehabilitation; in the second phase, 19 professionals were interviewed. Regarding sample characteristics, 59% of participants were between 31 and 40 years old, and 64.8% had completed postgraduate specialization programs, particularly in the areas of wheelchair provision, assistive technology, and orthoses. Concerning their workplaces, 56.5% were employed in rehabilitation centers and 44.4% in clinics, with most professionals working in two or more settings. Participants reported frequent use of both standardized instruments and tools developed within their own services. The Functional Independence Measure (FIM) was reported by 56% of the sample; however, when considering all instruments cited, it accounted for 13.4% of the total. Notably, 63.5% of the instruments primarily assess body structure and function domains, according to the International Classification of Functioning, Disability and Health (ICF). Among the most frequently reported therapeutic practices were exercises, performed by 75% of respondents. Qualitative findings indicated that institutional contexts—including practice settings, management, and service dynamics—impact the work of occupational therapists. Mastery of the ICF framework was observed as a means to enhance team communication; however, there was limited appropriation of Occupational Therapy theoretical models and critical reflection on their relevance to practice. Nevertheless, the concept of occupation was identified as guiding professional reasoning. Although most professionals reported additional training in assistive technology, its practical application—such as prescription, fabrication, or adaptation—was not frequent. The study concludes that it provides relevant contributions to the field of physical rehabilitation in Occupational Therapy and supports the strengthening of public policies aimed at adult rehabilitation. Furthermore, the data collection instrument used in the first phase proved to be important in promoting professional reflection on practice within the context of functional health and physical rehabilitation.
Current scenario of functional rehabilitation practices for adults through occupational therapy in Brazil
Keywords: Terapia Ocupacional; Prática profissional; Reabilitação; Saúde do Adulto; Adult Health; Rehabilitation; Occupational Therapy; Professional Practice; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar